Profile of sexually transmitted infections among attendees of special clinics (Suraksha) at an apex regional sexually transmitted disease centre in North India – a five-year study - Muralidhar, Sumathi (2024)
Introduction: Sexually transmitted infections (STIs) present significant global and national health challenges, particularly in India. Objective: To estimate the prevalence and characteristics of STIs among attendees at the Suraksha Clinic in the Apex Regional STD Centre, Safdarjung Hospital. Methods: Retrospective data from January 2018 to December 2022 were statistically analyzed using Excel and SPSS. The study included the examination for diagnosis of various STIs, such as syphilis, human immunodeficiency virus (HIV), gonorrhoea, chlamydiasis, trichomoniasis, candidiasis, bacterial vaginosis, chancroid, and genital herpes. Gender distribution and syndromic diagnoses, including vaginal/cervical discharge and genital ulcers, were also considered. Referrals to Integrated Counseling and Testing Centres for HIV testing were analyzed. Results: The outcomes reveal a substantial burden of STIs, with 3.06% showing reactivity to syphilis, 1.74% testing positive for HIV, 3.36% for gonorrhoea, 11.78% for chlamydiasis, 1.05% for trichomoniasis, 26.24% for candidiasis, 9.97% for bacterial vaginosis, 7.80% for chancroid, 11.64% for herpes genitalis, and 4.01% for other non-STIs. Attendees' interactions included 34.36% of referrals to Integrated Counseling and Testing Centres for HIV testing. The gender distribution showed 58.92% male and 40.94% female attendees. Conclusion: Syndromic diagnoses, including vaginal/cervical discharge (21.22%) and genital warts (8.00%), highlight prevalent conditions, necessitating routine screening, early detection, and targeted interventions for effective disease control and prevention. These findings underscore the significance of integrated screening, patient education, and proactive strategies to safeguard public health in the face of rising STI rates.